Binary Eluent Based Vortex-Assisted Matrix Solid-Phase Dispersion for the Extraction and Determination of Multicomponent from Musk by Gas Chromatography-Mass Spectrometry - Shanshan Wang; Ye Shang; Chunxiao Liang; Tao Liu; Kunze Du; Jiading Guo; Jin Li; Yan-xu Chang (Journal of Analytical Methods in Chemistry)
A green, flexible, and effective strategy was proposed to quantify four target compounds (muscone, ethyl palmitate, ethyl oleate, and ethylparaben) from musk by binary eluent based vortex-assisted matrix solid-phase dispersion (MSPD) extraction coupled with GC/MS. Single-factor tests and orthogonal design were employed to optimize the MSPD parameters. In addition, the binary eluent system, methanol, and ethyl acetate 3 : 7 (v/v) were used to extract the target analytes. Finally, C18 was applied as the easily available dispersant and the sample powder was ground for 2 min. Thereafter, the mixture was rapidly extracted with the binary eluents under whirling for 3 min. Eventually, the analysis of the samples was completed within 12 min by GC/MS. All correlation coefficients (r) of four targets were more than 0.9991. The recoveries of all target compounds ranged from 92.8% to 101% while their RSDs were less than 6.94%. There was no significant matrix interference for the analysis. Thus, the combination of vortex-assisted MSPD with GC/MS was considered as a novel, rapid, and environmentally friendly quantitative approach for musk samples.